ANALISIS PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN DALAM MENGGUNAKAN JASA TRANSPORTASI ONLINE GRAB (Studi Kasus pada Mahasiswa Prodi S1 Manajemen 2016 Fakultas Ekonomi Universitas Singaperbangsa Karawang) - Nur Aeni (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
The purpose of this research is to find out whether the existence of good service quality and price can affect GRAB customer satisfaction, especially in 2016 students of S1 Management Study Program, Faculty of Economics, University of Singaperbangsa Karawang. The research method used is descriptive and verification methods, namely: collecting, presenting, analyzing, and testing hypotheses, as well as making conclusions and suggestions. The sample used was 193 respondents. Methods of data analysis using validity, reliability and normality tests, classical assumptions, multiple linear regression and hypothesis testing. Based on the results of statistical testing, the following results were obtained: Service quality has a positive and significant impact on customer satisfaction. Price has a positive and significant effect on customer satisfaction. Service quality and price Simultaneously using the F test is known to have a positive and significant effect on customer satisfaction in using GRAB online transportation services for students of the 2016 S1 Management Study Program, Faculty of Economics, University of Singaperbangsa Karawang. Keywords: Customer Satisfaction;Price; Service Quality